Premature ovarian failure - Stachowiak, Grzegorz; Zając, Agnieszka; Wilczyński, Jacek (Menopause Review/Przegląd Menopauzalny, 2012)
This article presents newest information on premature ovarian failure (POF), including patients’ characteristics, risk factors, diagnostic methods, reference to specific disease entities as well as remote consequences of chronic hypoestrogenism. The authors emphasize the necessity of quick and proper diagnosis of POF together with implementation of a suitable therapy, i.e. HRT or hormonal contraception.